Strategi Pengelolaan Pengembangan Kawasan Penyangga sebagai Hutan Cadangan Mangrove (Studi Kasus Ekosistem Mangrove Sungai Liung Kecamatan Bantan Kabupaten Bengkalis) - Miswadi, Miswadi; Siregar, Sofyan Husein; Siregar, Yusni Ikhwan (Dinamika Lingkungan Indonesia, 2015)
This study aims to formulate management strategies of mangrove buffer zonedevelopment of Liung River of Bengkalis Island for mangrove agroforestry. Research hasbeen conducted at mangrove areas of Liung River from February 23 through May 27, 2014.The research method is a survey method with descriptive analysis approach. Primary datawere collected through observation and in-depth interviews with a structured questionnaireinstrument. Secondary data were obtained from the relevant department of this research.RapidEye Satellite Imagery Analysis is used to determine the total area of mangrove LiungRiver and the buffer area and the development of strategies using SWOT anilysis. Theanalysis showed that the area of land covering an area of 609.5 hectares of mangrove bufferthe potential for development of mangrove agroforestry which is done in order to reduce thepressure on mangrove forests of Liung River and the opportunity to engage the community inmeeting the needs of mangrove woods. Priority strategies related to the management ofmangrove agroforestry development in principle in the position of management models thatare included in the category of growth and stability strategy, ie a strategy that is implementedwithout changing the direction of a predetermined strategy. It is need the support of localgovernments and other institutions and communities in the implementation of sustainabledevelopment.